School and Sociology of Religious Education: Practice Study of Internalizing Multicultural Values - Masyitoh, Siti; Muhammad, Sakira (JURNAL INDO-ISLAMIKA, 2024)
This study aims to analyze the concepts, steps, and practices of internalizing multicultural values in Religious Education using a qualitative case study approach. Participants include school principals, vice principals, religious education teachers, guidance counselors, and students. Data collection methods encompass observation, interviews, and documentation, with analysis following reduction stages, data display, verification, and conclusion drawing. The research concludes that internalizing multicultural values in Religious Education involves embedding them into an intrinsic part of students' identities. The process is executed through value transformation, value transactions, and trans-internalization, progressing from simple to complex stages. This internalization is facilitated through the curriculum, teaching methods, extracurricular activities, and a hidden curriculum. The results indicate that success in internalizing these values depends on a gradual process encompassing cognitive, affective, and psychomotor domains, ultimately fostering a multicultural pluralist personality among students through consistent socio-religious behavior.